1994
DOI: 10.1128/mcb.14.7.4419
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A acts at multiple points to inhibit Xenopus oocyte maturation.

Abstract: In Xenopus oocytes, initiation of maturation is dependent on reduction of cyclic AMP-dependent protein kinase (PKA) activity and the synthesis of the mos proto-oncogene product. Mos is required during meiosis I for the activation of both maturation-promoting factor (MPF) and mitogen-activated protein kinase (MAPK).Here we show that injection of the catalytic subunit of PKA (PKAc) The events of maturation, including germinal vesicle breakdown (GVBD), chromosome condensation, and formation of the metaphase spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 62 publications
(58 reference statements)
8
88
0
Order By: Relevance
“…Recently, it was proposed that PKA may have pleiotropic e ects and inhibit oocyte maturation at multiple points (Matten et al, 1994;Rime et al, 1994). One of these e ects was proposed to be the inhibition of endogenous c-mos synthesis, another e ect the suppression of cdc25 activation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it was proposed that PKA may have pleiotropic e ects and inhibit oocyte maturation at multiple points (Matten et al, 1994;Rime et al, 1994). One of these e ects was proposed to be the inhibition of endogenous c-mos synthesis, another e ect the suppression of cdc25 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cell-free system prepared from Xenopus oocytes, Van Renterghem et al (1994) reported that pretreatment of extracts with PKAc had no e ect on the ability of cmos to activate MAPK, suggesting that both the direct activation of MAPKK by c-mos and the activation of MAPK by MAPKK are insensitive to PKA. In contrast, Matten et al (1994), using microinjection into oocytes, reported that microinjected PKAc decreased activation of MAPK by microinjected cmos to 50% of the control level.…”
Section: Pka Suppresses Mpf Activation But Does Not Reduce the Extentmentioning
confidence: 92%
See 3 more Smart Citations